Optimisation of laser beam cutting parameters of high density composite fibre cement flat board - Molnár, László; Csiszér, Tamás; Borbás, Lajos; Bognár, Levente L. (Materials today : proceedings, 2019)
At the beginning of the research work we encountered two major problems. First, literature for laser beam machining of fibre cement is virtually zero. This fact does not exclude the research of the subject by others, of course, but it may in any case indicate its confidentiality (technological competitive advantage). Second, the exact composition of the fibre cement material is protected, but the boards we use are available from manufacturer by code number, so the experiment can be clearly reproduced. For this reasons, we have decided to use the rigid, classic Design of Experiments method. Based on our previous experience, the effect factors were chosen in the group of Laser power, Cutting velocity, Cutting gas pressure, Focal length, Laser frequency and Cutting gas type, at a total of 17 factor levels. The necessary and sufficient conditions are met by the 2-Factor-Interaction (2FI) fractional factorial experiments, instead of full factorial 6FI experiment series. Based on our very first experiments, it was found that the high-density composite fiber cement material can be cut with laser beam technology. Experiments and related visual and measurement responses clearly define the significant effect factors. The experiments proved our zero hypotheses, the “p-values”, derived from the analysis of the response parameters, were below 0.05% (the significance limit usually is 0.1%), for each responses. We answered the questions of the fastest and cheapest technology lineup, to laser beam cut a composite fibre cement board to the desired size, with the expected quality.